A multi-way parallel named entity annotated corpus for English, Tamil and Sinhala - Surangika Ranathunga; Asanka Ranasinghe; Janaka Shamal; Ayodya Dandeniya; Rashmi Galappaththi; Malithi Samaraweera (Natural Language Processing Journal)
This paper presents a multi-way parallel English-Tamil-Sinhala corpus annotated with Named Entities (NEs), where Sinhala and Tamil are low-resource languages. Using pre-trained multilingual Language Models (mLMs), we establish new benchmark Named Entity Recognition (NER) results on this dataset for Sinhala and Tamil. We also carry out a detailed investigation on the NER capabilities of different types of LMs. Finally, we demonstrate the utility of our NER system on a low-resource Neural Machine Translation (NMT) task. Our dataset is publicly released: https://github.com/suralk/multiNER.